Design and evaluation of degenerate primers targeting the NS3 gene for detection of dengue virus by RT-PCR - Saefuddin Aziz; Regita Cahaya Sari; Dwi Priyanto; Tri Ramadhani (Indonesian Society for Biochemistry and Molecular Biology, 2025)
Background: Dengue fever, caused by the dengue virus, is hyper-endemic in Indonesia. Since no protective vaccine or specific treatments are available, accurate diagnosis is crucial for the early implementation of preventive measures to limit dengue transmission and reduce economic losses. Various diagnostic techniques have been developed, including reverse transcriptase-polymerase chain reaction (RT-PCR) for detecting viral nucleic acids using specific primers. Objective: This study aimed to design and evaluate the effectiveness of a new primer targeting the NS3 gene of the dengue virus for molecular detection in clinical samples. Methods: A cross-sectional molecular study was conducted in Banjarnegara, Indonesia. Serum samples were collected from dengue-suspected patients attending hospitals in the city. The diagnosis was initially performed using dengue NS1 antigen and IgG/IgM antibody detection. Dengue virus (DENV) serotyping was conducted using Simplexa Dengue real-time RT-PCR with a newly designed NS3 gene primer. The effectiveness of the new primer was assessed by comparing its performance with a commercial primer. Results: The primers, DenVNS3F (5’-CGAGTAGGAATGGGWGARGCAGC-3’) and DenVNS3R (5’-CTGTCCAGTGAGCRYGGTCTT-3’) were able to detect the NS3 gene of the dengue virus. However, the level of agreement in detecting the dengue virus compared to the commercial primer showed a moderate agreement (k = 0.60) with a low confidence level. Conclusion: The newly designed primers DenVNS3F and DenVNS3R are capable of detecting the NS3 gene. However, the primers may require further optimization to achieve a higher level of accuracy and confidence in detecting the dengue virus, and additional validation through sequencing is necessary to confirm the specificity of the amplified product.